Analysis Of The Influence Of Organizational Culture, Communication And Work Stress On Employees' Work Performance At The Education Foundation Of Dr Wahidin Sudirohusodo Medan - Sahat Simbolon; Rusdiana Simamora (International Forum of Researchers and Lecturers, 2023)
The objective of this study is to examine the impact of organizational culture, communication, and job stress on the performance of employees at Yayasan Perguruan Dr. Wahidin Sudirohusodo Medan. We employed a survey methodology by administering a questionnaire to a sample of employees from the foundation, picked at random. The acquired data was examined using regression techniques to ascertain the correlation between the variables under study. The analytical findings suggest that a favorable company culture exerts a substantial impact on employee performance. The values, conventions, and behaviors within a corporate culture have a significant impact on enhancing employee motivation, engagement, and performance. Furthermore, the establishment of efficient communication channels between management and employees is also crucial in enhancing work performance by fostering a clearer comprehension of organizational objectives, job responsibilities, and valuable input. Nevertheless, research has demonstrated that work-related stress has a detrimental impact on the performance of employees. Elevated levels of stress can disrupt employee focus, drive, and psychological well-being, resulting in diminished productivity and job excellence. These findings indicate that Yayasan Perguruan Dr. Wahidin Sudirohusodo Medan's management should strengthen a favorable organizational culture by emphasizing the principles of cooperation, creativity, and employee assistance.